Pompan: A bread production alternative using apple pomace - Beatriz Coelho; Inês Oliveira; Isabel Mota; João Nunes; Sofia Coelho; Tiago Mendes (U.Porto Journal of Engineering)
This work consists of developing a product that uses apple leftovers. The product selected was bread baked with a flour mixture of 5% (by mass) apple flour to wheat flour. Besides providing an easy-to-use solution for leftovers, this mixture also provides a higher fiber content to the food. After the process was designed, it was concluded that producing 5.4 million breads per year with about 23 tons of apple pomace was possible. In the end, the economic analysis was done, and the process should return a profit at the beginning of the second year, having an NPV of 0.88 M€, an IRR of 27.8% and a payback time of almost 4 years.